Mesenchymal Stem Cells Combined With IFN gamma Induce Apoptosis of Breast Cancer Cells Partially Through TRAIL - AKKOÇ, TUNÇ (INT INST ANTICANCER RESEARCH, 2020)
Background: Mesenchymal stem cells (MSCs) have gained remarkable attention because of their ability to dualistically regulate tumor growth. The main objective of this study was to evaluate the apoptotic effects of human bone marrow-derived (hBM) MSCs in combination with interferon gamma (IFN-gamma) on MCF-7 breast cancer cells, and to determine the cytokines involved in the apoptotic process. Materials and Methods: hBM-MSCs were co-cultured with MCF-7 cells either directly and indirectly for 72 h in-vitro. Levels of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), apoptosis and cytokines were analyzed. Results: hBM-MSCs increased the apoptosis of MCF-7 cells partially through TRAIL in vitro. IFN-gamma enhanced the apoptotic effect of hBM-MSCs (p<0.001). Conclusion: hBM-MSCs in combination with IFN-gamma might be a suitable therapy for breast cancer.
Keywords: MCF-7; breast cancer; mesenchymal stem cells; TRAIL; INTERFERON-ALPHA; METASTASIS; GROWTH; PROMOTE